Growth in East Asia : what we can and what we cannot infer - Sarel, Michael (Economic issues (International Monetary Fund), 1996)
The following paper draws on material originally contained in IMF Working Paper 95/98, "Growth in East Asia: What We Can and What We Cannot Infer From It," by Michael Sarel, an Economist in the Fund's Southeast Asia and Pacific Department. It has been prepared by David D. Driscoll of the Fund's External Relations Department.